Programa Mais Educação: uma política progressista de educação integral em tempo integral - Soares, José Nildo Oliveira (2020)
This research took as its object of study the More Education Program (Programa Mais Educação - PME) (2007-2016), one of the public education policies of Lula (2003- 2010) and Dilma’s (2011-8 / 2016) governments. It focused on the experience of public schools in the city of Santana de Parnaíba, located in the state of São Paulo, Brazil, in Elementary Schools (2013-2019). This study is part of the investigations carried out by Curricular Justice Study and Research Group (Grupo de Estudos e Pesquisa em Justiça Curricular - GEPEJUC) led by PhD Professor Branca Jurema Ponce from the Education Program: Curriculum at the Pontifical Catholic University of São Paulo. It was developed from preliminary research in legislation and official documents. This was followed by three stages of surveying academic productions on the topic: in Doctoral Dissertations, Master’s thesis and Academic Papers. The field research included interviews with managers, coordinators, workshopers, students and those responsible for them who participated in the More Education Program of Santana de Parnaíba, as well as an interview with the More Education Program manager in the city of Araras (2009-2016), São Paulo. A total of 23 interviews were conducted. To approach the object, studies were carried out on Integral Education (BRASIL, 2009a, 2009b, 2009c; ARROYO, 2012; CAVALIERE, 2010a; GADOTTI, 2009; MAURÍCIO, 2009; MOLL, 2012a, 2012b, 2013). The following categories of historical materialism were used in the analysis: totality, contradiction, praxis and mediation (CURY, 1989; FRIGOTTO, 2008; GADOTTI, 2012). The concept of curricular justice in its three dimensions was also used in the analyzes: knowledge, coexistence and care (CONNEL, 1995, 1997; DUBET, 2004, 2008a, 2008b; PONCE, B. J., 2016a, 2016b, 2018; PONCE; ARAÚJO, 2019; TORRES SANTOMÉ, 2013). The results point to the More Education Program as a progressive educational policy that, in Santana de Parnaíba, articulated itself with other social policies without losing its specificity as a policy to induce full-time comprehensive education, as its praxis were developed from a curriculum that included school, community and cultural knowledge, and expanded educational experiences and the resizing of school times and spaces, in order to present itself as an articulated and effective educational policy for the comprehensive formation of the subject. It is also concluded that the More Education Program, like other democratic experiences lived in the history of Brazilian Education, leaves legacies of hope steeped in the certainty that it is possible to build social quality education in Brazilian school networks, for the subjects of education, for the school institution and for all who believe in public schoo